2007
DOI: 10.1890/06-1182.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Seawater Temperature Variation on Coral Bleaching and Mortality

Abstract: Abstract. Coral bleaching due to thermal and environmental stress threatens coral reefs and possibly people who rely on their resources. Here we explore patterns of coral bleaching and mortality in East Africa in 1998 and 2005 in a region where the equatorial current and the island effect of Madagascar interact to create different thermal and physicochemical environments. A variety of temperature statistics were calculated, and their relationships with the degree-heating months (DHM), a good predictor of coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
211
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(225 citation statements)
references
References 91 publications
(177 reference statements)
11
211
2
1
Order By: Relevance
“…2016, 8,12 3 Atlantic coastlines. Buccoo Reef extends to 3 km offshore and consists of a shallow lagoon ranging in depths from 2-6 m containing several patch reefs and reef flats, with corals also present on the reef slope to 20 m depth [26].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…2016, 8,12 3 Atlantic coastlines. Buccoo Reef extends to 3 km offshore and consists of a shallow lagoon ranging in depths from 2-6 m containing several patch reefs and reef flats, with corals also present on the reef slope to 20 m depth [26].…”
Section: Study Areamentioning
confidence: 99%
“…These events have threatened to reduce fishery population [3,4], while simultaneously affecting the economic benefits of tourism that supports many coastal communities [5,6]. Effective management of coral reefs and associated ecosystem services has been aided in recent decades by satellite remote sensing monitoring that provides near real-time sea temperature (SST) data and customized products [7][8][9][10][11][12][13]. Mass coral bleaching has been related to anomalously high sea temperatures and has resulted in increased mortality of corals globally [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…One example of the benefits of such an approach comes from Puerto Rico, where a combination of temperature metrics -rather than simply the maximum seawater temperature, and the duration of exposure to this value (Gleeson and Strong, 1995) -provided the best predictor of coral bleaching between 1966 and 1995 (Winter et al, 1998). Similarly, off the coast of East Africa, coral bleaching was associated with degree heating weeks, degree heating months, and the variability as assessed by the standard deviation and kurtosis of the monthly mean records of sea surface temperature (SST) (McClanahan et al, 2007). Together, studies such as those of Winter et al (1998) and McClanahan et al (2007) indirectly suggest that the thermal history of a coral matters a great deal in determining its response to thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, off the coast of East Africa, coral bleaching was associated with degree heating weeks, degree heating months, and the variability as assessed by the standard deviation and kurtosis of the monthly mean records of sea surface temperature (SST) (McClanahan et al, 2007). Together, studies such as those of Winter et al (1998) and McClanahan et al (2007) indirectly suggest that the thermal history of a coral matters a great deal in determining its response to thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several studies have revealed that the decline of corals has resulted in shifts in dominance from hard corals to macro algae and other sessile invertebrate dominated benthic functional groups in many regions of the world [10]. made in 2002 [2,3,11,12]. Since, coral cover is important to gauge the overall health and general status of a reef in relation to shifting dominance, ecological processes and economic services provided to human communities [9,13].…”
Section: Introductionmentioning
confidence: 99%